Prosthetic valve thrombosis in a tertiary cardiac centre - Hirachan, Anish; Roka, Madhu; Prajapati, Dipanker; Adhikari, Chandra Mani; K.C., Bishal; Khadka, Manjila Basnet; Maskey, Arun; Sharma, Deewakar (Nepalese Heart Journal, 2017)
Background and Aims: Prosthetic valve thrombosis remains a major complication of valve replacement surgeries in Nepal. A number of patients present with thrombotic complications mainly due to poor anticoagulation status with irregular INR checkup at the remote areas of Nepal. Thrombolysis is the preferred method in the management of stuck valve patients due to financial issues . We aimed to retrospectively study the clinical profile and management trends of stuck prosthetic valve Methods: A one year retrospective data of 23 patients (Jan 2015 - Jan 2016) admitted with diagnosis of prosthetic valve thrombosis were studied. The demographic profile, clinical parameters and in hospital outcome were analysed. Results: Out of 23 patients, majority were female (52.2%) with the age group 13-49 years (mean = 35). Sixteen patients (69.6%) presented with INR value < 1.5 at admission. Twenty patients ( 86.9%) were thrombolysed with streptokinase while 3 patients ( 13.1 %) were subjected to treatment with tenecteplase . Valve thrombosis was most common at the mitral position 17 (73.9%) patients. In hospital mortality was seen in 5 ( 21.7%) patients and there were no major bleeding events or new stroke noted. Conclusion: Majority of patients with prosthetic valve thrombosis presented with a subtherapeutic INR value. Thrombolysis can be a useful option in the management of prosthetic valve thrombosis patients in a less resourceful country. Nepalese Heart Journal 2017; 14(1): 9-11